Site-Specific In Situ Synthesis of Eumelanin Nanoparticles by an Enzymatic Autodeposition-Like Process - Strube, Oliver I.; Büngeler, Anne; Bremser, Wolfgang (Biomacromolecules)

Synthesis of polyamide-imide-montmorillonite-nanocomposites via new approach of in situ polymerization and solvent casting - Briesenick, Daniel; Bremser, Wolfgang (Progress in Organic Coatings)

A Metric for Candidate Selection for a Robust Opportunistic Container Routing in high Complex Distribution Centers - Kopecki, Lukas

A Technical Approach of a Simulation-Based Optimization Platform for Setup-Preparation via Virtual Tooling by Testing the Optimization of Zero Point Positions in CNC-Applications - Weber, Jens (Proceedings of the 2015 Winter Simulation Conference)

A Comparison of the Usage of Different Approaches for the Management of Plant Engineering Projects - Akbulut, Akin; Laroque, Christoph; Wenzel, Sigrid; Jessen, Ulrich (Proceedings of the 2015 Winter Simulation Conference)
Customized planning, engineering and construction of one-of-a-kind products (like wind energy, biogas or power plants) are complex and contain a lot of risks and temporal uncertainties, e.g. of logistics and project schedules. Therefore the management of this kind of projects has to be supported by adequate methods for the estimation of project risks and uncertainties. Based on the results of the joint research project simject of the Universities of Paderborn and Kassel, which aims at the development of a demonstrator for simulation-based and logistic-integrated project planning and scheduling, this paper discusses the usage of different approaches for supporting project management of plant engineering projects. After a short introduction and description of the approaches to be compared a wind energy plant as evaluation model as well as the application of the different methods are presented. Additionally, the usage of the approaches is compared and the advantages and disadvantages are pointed out.

A Deadlock-Free Route Reservation Method for Automatized Decentralized Controlled Transportation in High Complex Distribution Centers - Kopecki, Lukas

Sharing Means Caring? Hosts' Price Reactions to Rating Visibility - Gutt, Dominik; Herrmann, Philipp (Proceedings of the 23rd European Conference on Information Systems (ECIS), Münster)
We empirically investigate how hosts on Airbnb, a popular peer-to-peer website for fee-based sharing of under-utilized space, adjust their prices once their offering gets a visible star rating for the first time. We use data for over 14,000 offerings from Airbnb which we collected for New York City. Our findings indicate that hosts whose offerings achieve star rating visibility significantly increase their prices by an average of 2.69 € more than hosts with comparable offerings who do not experience this rating visibility during the time of observation. Out of all offerings who achieve rating visibility, we identify the upper quartile of hosts to be the main driver of this price increase, whereas the first 75% percent show only a marginal price reaction. These results can serve as a first step towards understanding the motivation of people to provide assets to the sharing economy.

A Robust Opportunistic Routing for High complex Decentralized controlled Distribution Center - Kopecki, Lukas

Implementation and Comparison of Cluster-Based PSO Extensions in Hybrid Settings with Efficient Approximation - Mueß, André; Weber, Jens; Reisch, Raphael-Elias; Jurke, Benjamin (Proceedings of the First Conference of Machine Learning for Cyber Physical Systems)

Protocol Structure for Controlling Adaptive Conveyor System in Automatized High Complex Distribution Centers - Kopecki, Lukas

A System for Uncovering Latent Connectivity of Health Care Providers in Online Reviews - Baeumer, Frederik Simon; Geierhos, Michaela; Schulze, Sabine (Information and Software Technologies: 21th International Conference, ICIST 2015, Druskininkai, Lithuania, October 15-16, 2015, Proceedings)

Find a Physician by Matching Medical Needs described in your Own Words - Baeumer, Frederik Simon; Dollmann, Markus; Geierhos, Michaela

An approach for deadlock Prevention in decentralized controlled pre-storage zones with dynamic behavior and time windows - Kopecki, Lukas (International Journal of Materials, Mechanics and Manufacturing)

Der zufriedene Patient 2.0: Analyse anonymer Arztbewertungen im Web 2.0. - Geierhos, Michaela; Schulze, Sabine; Baeumer, Frederik Simon (Working Papers des KVF NRW)

Online-Optimierung zur Festlegung von Bestellzeitpunkten in der Losgrößenfertigung - Dangelmaier, Wilhelm (Schenk, Michael;Zadek, Hartmut;Müller, Gerhard;Richter, Klaus;Seidel, Holger (Hrsg.): 20. Magdeburger Logistiktage "Sichere und nachhaltige Logistik")

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Baeumer, Frederik Simon; Sabine, Schulze; Valentina, Stuß (Current Approaches in Applied Artificial Intelligence, Lecture Notes in Computer Science)

I grade what I get but write what I think." Inconsistency Analysis in Patients‘ Reviews - Geierhos, Michaela; Baeumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (ECIS 2015 Completed Research Papers)

Hardware in the Loop Framework for decentralized autonomous conveyor in automatic pre-storage zones - Kopecki, Lukas

Share Economy - Identifikation von konstituierenden Merkmalen anhand einer vergleichenden Betrachtung von Geschäftsmodellen - Trykacz, Matthias

Asynchronous Optimization Techniques for Distributed Computing Applications - Reisch, Raphael-Elias; Weber, Jens; Laroque, Christoph; Schröder, Christian (Proceedings of the 2015 Spring Simulation Multi-Conference)